Mechanisms and Rescue Strategies of Calcineurin Inhibitor Mediated Tolerance Abrogation Induced by Anti‐CD4 mAb Treatment. Issue 9 (15th July 2013) - Siepert, A.; Brösel, S.; Vogt, K.; Ahrlich, S.; Schmitt‐Knosalla, I.; Loddenkemper, C.; Kühl, A.; Baumgrass, R.; Gerstmayer, B.; Tomiuk, S.; Tiedge, M.; Viklický, O.; et al.
Abstract: To ensure safety tolerance induction protocols are accompanied by conventional immunosuppressive drugs (IS). But IS such as calcineurin inhibitors (CNI), for example, cyclosporin A (CsA), can interfere with tolerance induction. We investigated the effect of an additional transient CsA treatment on anti‐CD4mAb‐induced tolerance induction upon rat kidney transplantation. Additional CsA treatment induced deteriorated graft function, resulting in chronic rejection characterized by glomerulosclerosis, interstitial fibrosis, tubular atrophy and vascular changes. Microarray analysis revealed enhanced intragraft expression of the B cell attracting chemokine CXCL13 early during CsA treatment. Increase in CXCL13 expression is accompanied by enhanced B cell infiltration with local and systemic IgG production and C3d deposition as early as 5 days upon CsA withdrawal. Adding different CNIs to cultures of primary mesangial cells isolated from glomeruli resulted in a concentration‐dependent increase in CXCL13 transcription. CsA in synergy with TNF‐α can enhance the B cell attracting and activating potential of mesangial cells. Transient B cell depletion or transfer of splenocytes from tolerant recipients 3 weeks after transplantation could rescue tolerance induction and did inhibit intragraft B cell accumulation, alloantibody production and ameliorate chronic rejection. Abstract : Transient coapplication of cyclosporine A abrogates CD4‐specific monoclonal antibody‐mediated transplant tolerance by inducing intragraft CXCL13 expression leading to B cell attraction, alloantibody production and complement‐mediated tissue destruction.